A Multifunctional Subphthalocyanine Nanosphere for Targeting, Labeling, and Killing of Antibiotic‐Resistant Bacteria. (23rd October 2015) - Roy, Indranil; Shetty, Dinesh; Hota, Raghunandan; Baek, Kangkyun; Kim, Jeesu; Kim, Chulhong; Kappert, Sandro; Kim, Kimoon
Abstract: Developing a material that can combat antibiotic‐resistant bacteria, a major global health threat, is an urgent requirement. To tackle this challenge, we synthesized a multifunctional subphthalocyanine (SubPc) polymer nanosphere that has the ability to target, label, and photoinactivate antibiotic‐resistant bacteria in a single treatment with more than 99 % efficiency, even with a dose as low as 4.2 J cm −2 and a loading concentration of 10 nM . The positively charged nanosphere shell composed of covalently linked SubPc units can increase the local concentration of photosensitizers at therapeutic sites. The nanosphere shows superior performance compared to corresponding monomers presumably because of their enhanced water dispersibility, higher efficiency of singlet‐oxygen generation, and phototoxicity. In addition, this material is useful in fluorescence labeling of living cells and shows promise in photoacoustic imaging of bacteria in vivo.